Effects of different kinds of fertilizers on production of fishes in Polyculture system (International Journal of Agricultural Research, Innovation and Technology, 2015)
A study was conducted to assess the effects of different kinds of inorganic fertilizers on the production of fishes in six ponds during October to December 2011. There were three treatments with two replications under each treatment and each of the ponds was stocked with 80 fish fry. In treatments I, II and III, ponds were fertilized fortnightly @ urea 100 g decimal-1, T.S.P. 100 g decimal-1 and urea 50 g decimal-1 + T.S.P. 50 g decimal-1, respectively. Selected water-quality parameters of ponds under study were more or less similar and within the productive range. Mean phytoplankton and zooplankton densities under treatments I, II and III were 57.08 ± 1.35, 8.80 ± 0.09 and 77.29 ± 3.72, 12.88 ± 0.74 and 98.93 ± 1.61, 16.16 ± 1.75 (x103) cells L-1, respectively. The net and gross fish productions of the ponds under treatments I, II and III were 0.85 and 3.11 t ha-1 yr-1 and 1.32 and 3.58 t ha-1 yr-1 and 1.85 and 4.11 t ha-1 yr-1, respectively. Fish production under treatment III was better than those under treatments I and II because plankton population densities under treatment III was the highest. Therefore, the mixed fertilization is suitable for production of plankton that enhance growth and production of fishes. DOI: http://dx.doi.org/10.3329/ijarit.v4i2.22639 Int. J. Agril. Res. Innov. & Tech. 4 (2): 16-21, December, 2014